Diagnosis and Outcome of Cardiac Paragangliomas: A Retrospective Observational Cohort Study in China - Dong, Xueqi; Meng, Xu; Zhang, Ting; Zhao, Lin; Liu, Fang; Han, Xu; Liu, Yecheng; Zhu, Huadong; Zhou, Xianliang; Miao, Qi; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac paragangliomas (CPGLs) are rare neuroendocrine tumors that are easily overlooked and difficult to diagnose. Detailed comprehensive data regarding CPGL diagnosis and outcome are lacking. Methods: We retrospectively analyzed a cohort of 27 CPGL patients. This cohort represents the largest such cohort reported to date. Comparisons were made with a group of 59 pheochromocytoma (PHEO) patients. Results: The prevalence of concurrent palpitations, hyperhidrosis, and headache was more frequent in the CPGL group (33.3% vs. 13.6%; P = 0.033). Sensitivity of echocardiography and contrast-enhanced computed tomography for localization of CPGL were 81.8% and 87%, respectively. Sensitivity of octreotide scintiscan was significantly higher for CPGL than for PHEO (100%. vs. 70.8%; P = 0.004); conversely, sensitivity of I131-metaiodoben-zylguanidine (MIBG) scintigraphy was higher for PHEO (90.2% vs. 32.9%) than for CPGL. Prevalence of multiple tumors was significantly higher in the CPGL group than that in the PHEO group (29.6% vs. 10.2%; P = 0.023). Most CPGLs originated from the epicardium or the root of the great vessels (92.9%) and were mostly supplied by the coronary arteries and their branches (95.7%). Twenty-five of 28 CPGLs (1 patient had 2 tumors) underwent surgical treatment. Local invasion was more prevalent in CPGLs than in PHEOs (40.0% vs. 11.5%; P = 0.035). Local invasion did not affect long-term outcome in CPGL patients. Mean follow-up was 6.9 ± 3.6 years. Biochemical remission was achieved in 85% of CPGL patients. The recurrence rate was 15%. Conclusions: Manifestations of CPGLs are non-specific, and they can be difficult to detect on imaging examinations. Both MIBG and octreotide scintiscan should be performed in patients with suspected paragangliomas to screen for multiple lesions. Surgical resection of CPGLs can achieve symptom relief and biochemical remission.